Subsurface Characterization Using Multichannel Analysis of Surface Waves (MASW) for Coastal Abrasion Mitigation and Geotourism Planning at Nangai Beach, North Bengkulu - Insani, Redha Radiatul; Hadi, Arif Ismul; Farid, Muchammad; Raihana, Hana; Al Ansory, Andre Rahmat; Muammar, Zaky (Jurnal Meteorologi dan Geofisika, 2025)
Subsurface rock weakness is considered a contributing factor to the high abrasion rate along Nangai Beach, North Bengkulu. This study aims to characterize the subsurface structure using shear-wave velocity (Vs) data derived from Multichannel Analysis of Surface Waves (MASW) at 21 measurement points along the coastline. The data were processed using WinMASW 5.0 Professional software, beginning with dispersion curve picking in the fundamental mode and followed by inversion to generate one-dimensional Vs profiles along with corresponding density and layer thickness. Interpretation of the 1D and 2D Vs profiles indicates that most of the study area is dominated by soft rock formations with generally low Vs30 values, highlighting the area’s vulnerability to coastal abrasion. Recommended mitigation strategies include natural restoration through coastal vegetation, construction of protective structures, and implementation of regional zoning to safeguard tourism and residential areas. Furthermore, active community participation in tourism management is essential to achieve a sustainable balance between environmental preservation and economic development. Overall, the findings provide valuable input for local governments in designing effective abrasion mitigation strategies and sustainable geotourism development plans.